ANALISIS STRUKTUR MODAL DAN INVESTMENT TERHADAP KUALITAS LABA (STUDI PADA PERUSAHAAN REAL ESTATE DAN KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - AGUSTALINDA NORA; DIANA SARI; REZA OKTAVIA; ZULHAM IDRIS (JURNAL ILMIAH KOHESI, 2021)
The purpose of this research is to show the influence of capital structure analysis and investment on profit quality (study onreal estate companies, and building construction listed on the Indonesia stock exchange. Based on the results of statisticaltests using multiple regression analysis, partially variable liquidity has no effect on the quality of profit because it is seen fromthe significance value of 0.129 where the result is greater than the significant value of 0.129> 0.05 so that H1 is rejected.Partially variable size has no effect on the quality of profit because it is seen from the value of significance of 0.983 wherethe result is greater than the significant value of 0.983> 0.05 so that H2 is rejected. Partially the variable capital structure hasno effect on the quality of profit because it is seen from the significance value of 0.680 where the result is greater than thesignificant value of 0.680> 0.05 so that H3 is rejected. Partially variable invesment opportunity set (IOS) has no effect on thequality of profit because it is seen from the value of significance of 0.983where the result is greater than the significant valueof 0.983> 0.05 so that H4 is rejected. Simultaneously, variable liquidity, size, capital structure and investment opportunity setsimultaneously had no effect on the quality of profit because the significant value is greater than 0.05 i.e. 0.271 > 0.05 so H5is rejected.